Entre o evangelho e o ensino rural : educação feminina no Instituto Nossa Senhora do Calvário (Vale Do Guaporé/Guajará-Mirim MT/RO 1933 -1976) - Souza, Cleicinéia Oliveira de (2017)
This research is inserted in the area of Education and studies of historical character. The object of study is the school institution Institute of Our Lady of Calvary and the education that it offered to the women between the years of 1933 to 1976. The school was located in the city of Guajará-Mirim, located in the state of Mato Grosso until 1943 and closed its activities in 1976, at a time when the municipality was already part of the state of Rondônia. We set the chronological cut between the years of 1933 with the beginning of the activities of the College Santa Terezinha until the year of 1976 when the activities of the Institute of Our Lady of Calvary. The main focus was to investigate the female education that was offered to the girls and young women in the Institute of Our Lady of Calvary, to record and analyze the history of the Congregation of Our Lady of Calvary, the mission that they proposed in Guajará-Mirim and the trajectory of the institution According to the proposal of Don Francisco Xavier Rey for the formation of the girls. We tried to respond as did the female education offered at the school and we have as sources: a book of Chronicles written by one of the Sisters who came to found the Institute, diaries, bulletins, petitions, messages of the presidents of the state of Mato Grosso, newspapers , Reports and photographs that allowed us to establish the categories of analysis. This documentation was collected in different archives such as: Public Archive of Mato Grosso, Provincial House of the Congregation of Our Lady of Calvary in São Paulo, Brazil, General Archive of the Congregation of Our Lady of Calvary in Gramat, France, Museum Historical Municipal Guajará-Mirim, House of the Calvarian Sisters of Guajará-Mirim, among others. Authors such as Jacques Le Goff (1990), Marc Bloch (2002), Justino Pereira de Magalhães (2004), Paolo Nosella and Ester Buffa (2009), José D 'Assunção Barros (2008) have made it possible to understand History of Education It is necessary to go through the paths of memory, entering into the intricacies of history. The theoretical studies by Carlo Ginzburg (1989), Michel de Certeau (1998), Peter Burke (1997) have helped us to understand that it is possible to analyze aspects of an institution's daily life and to find clues, signs that help us compose a narrative about Events that are found in the records, in the sources on which we are based. The authors Michelle Perrot (2007), Jane Soares de Almeida (1998), Guacira Lopes Louro (1997), among others authors and authors contributed to analyze the history of female education and the process that women experienced in order to gain access to schooling. The analysis of the sources allowed us to infer that the teaching offered at the Our Lady of Calvary Institute was rigorously influenced by conservative religious principles. However, although the school institution was a private and confessional institution, it fulfilled a function that would belong to the State, since in the Federal Constitution of republican Brazil it was established that public education would be secular and gratuitous, yet the Institute of the Calvarian Sisters Promoted the schooling of the women who lived in the Guaporé Valley from 1933 to 1976.